2017
DOI: 10.4067/s0717-95022017000200026
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Morphology of Ghrelin-Immunopositive Cells in the Thymus of the African Ostrich

Abstract: Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor, has been detected in the thymus of multiple vertebrates. However, little is known about its distribution in the thymus of the African ostrich. In this study, we evaluated the distribution and morphological characteristics of ghrelin-producing cells in the thymus of the African ostrich. Our results revealed that the thymus consists of a capsule and a parenchyma, which comprises the cortex and medulla. Compared to the cortex, the medulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Since the structure and the function are closely related, the microstructure of different aged thymuses was explored by HE staining that showed a downtrend, except for a small increase at the 3 rd week, with significant alterations in ratio of the cortex to medulla. Similar changes in the aging thymus were also previously reported in rats [4143], African ostrich chicks [44, 45], and cynomolgus macaques [46, 47]. In addition, we also found an accumulation of adipose tissue while aging.…”
Section: Discussionsupporting
confidence: 90%
“…Since the structure and the function are closely related, the microstructure of different aged thymuses was explored by HE staining that showed a downtrend, except for a small increase at the 3 rd week, with significant alterations in ratio of the cortex to medulla. Similar changes in the aging thymus were also previously reported in rats [4143], African ostrich chicks [44, 45], and cynomolgus macaques [46, 47]. In addition, we also found an accumulation of adipose tissue while aging.…”
Section: Discussionsupporting
confidence: 90%
“…A large number of studies have confirmed the inference that the wide distribution of ghrelin immunopositive cells in animals may have many biological roles (Cardona et al 2012). Ghrelin immunopositive cells are widely distributed in the African ostrich (Wang et al 2017a;Wang et al 2017b;Ye et al 2018;Zhang et al 2018), Wang et al (2009) showed that ghrelin immunopositive cells are mainly distributed in the mucosal layer of the gastrointestinal tract of the African ostrich chicks and the number of immunopositive cells gradually decreases from the stomach to the small intestine and then to the large intestine. The number of ghrelin immunopositive cells in the small intestine also showed significant age-related changes, peaked at 90 days and then remained stable.…”
Section: Introductionmentioning
confidence: 89%
“…Ghrelin can regulate feeding and energy balance (Klok et al, 2007), promotes growth hormone release (Kojima et al), regulates cell proliferation, participates in immune antiinflammatory activities, and improves cardiovascular function. Studies have shown that ghrelin-immunopositive cells are widely distributed in African ostrich chicks (Ye et al, 2017;Wang et al, 2017a). Wang et al (2017b) reported that ghrelin-immunopositive cells are also found in the pancreas of African ostrich chicks; during the 1-90-day brooding period, the number of ghrelin-immunopositive cells decreased gradually with increasing age, which suggests that ghrelin acts as a signal that can influence developmental processes in the pancreas of African ostrich chicks.…”
Section: Introductionmentioning
confidence: 99%